UHPLC-MS Chemical Fingerprinting and Antioxidant, Enzyme Inhibition, Anti-Inflammatory In Silico and Cytoprotective Activities of Cladonia chlorophaea and C. gracilis (Cladoniaceae) from Antarctica - Alfredo Torres-Benítez; José Erick Ortega-Valencia; Marta Sánchez; Mathias Hillmann-Eggers; María Pilar Gómez-Serranillos; Gabriel Vargas-Arana; Mario J. Simirgiotis (Antioxidants, 2022)
The lichen species Cladonia chlorophaea and C. gracilis (Cladoniaceae) are widely distributed in the island archipelago of maritime Antarctica and represent a natural resource of scientific interest. In this work, the metabolomic characterization of the ethanolic extracts of these species and the determination of the antioxidant activity, enzymatic inhibition and anti-inflammatory potential of selected compounds on the 5-lipoxygenase enzyme by molecular docking and cytoprotective activity in the SH-SY5Y cell line were carried out. Nineteen compounds were identified by liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry (UHPLC-ESI-QTOF-MS) in each of the species. The contents of phenolic compounds, antioxidant activity, the inhibition of cholinesterases (acetylcholinesterase and butyrylcholinesterase) and digestive enzymes (α-glucosidase and pancreatic lipase) were variable among species, with better results in C. chlorophaea. Molecular docking evidenced significant binding affinities of some compounds for the 5-lipoxygenase enzyme, together with outstanding pharmacokinetic properties. Both extracts were shown to promote cell viability and a reduction in reactive oxygen species production in an H2O2-induced oxidative stress model. This study contributes to the chemical knowledge of the Cladonia species and demonstrates the biological potential for the prevention and promising treatment of central nervous system pathologies, inflammatory disorders and metabolic alterations.